Management of patients with acute pancreatitis In Al- Karama Teaching Hospital - Surriah, Mohammed H.; Hassan, Ahmed N.; Bakkour, Amine M. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Acute pancreatitis is an acute inflammatory condition. It's not an uncommon disease, in both the developed and developing countries, causes high morbidity and mortality, and inflicts a heavy economic burden. Severe acute pancreatitis is present in up to 25% of patients with acute pancreatitis, with considerable mortality. Changes in the management of acute pancreatitis in the last 2 decades contributed to reduce the mortality.Objective: was to review the diagnosis and management and outcomes of patients with acute pancreatitis of patients with acute pancreatitis in Al- Karama teaching hospital.Patients and Methods: This prospective study included 63 patients with acute pancreatitis in surgical and medical wards in Al- Karma teaching hospital from the 1st October 2014 to 30th September 2017.Results: 63 patients with acute pancreatitis were included 35 male and 28 female patients with upper abdominal pain in which the diagnosis was not confirmed by CT or serum amylase or by CRP are not included in this study. Age and gender had no significant relations to outcome. Medical therapy is the mainstay, with supportive therapy consisting of controlled volume resuscitation and enteral feeding. Minimally invasive drainage and debridement play a role in managing infective pancreatic necrosis but in general should not be used until at least 4weeks after the acute illness.Conclusions: Acute pancreatitis is a benign abdominal disorder in up to 85% of cases. In the remaining 10%-15% of cases the disorder is life threatening with management of the disorder requiring admission to an intensive care unit with cardiovascular, respiratory, and renal monitoring and support.